2011
DOI: 10.1021/la202113j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycine Substitution on Fmoc–Diphenylalanine Self-Assembly and Gelation Properties

Abstract: We have investigated the self-assembly behavior of fluorenyl-9-methoxycarbonyl (Fmoc)-FG, Fmoc-GG, and Fmoc-GF and compared it to that of Fmoc-FF using potentiometry, fluorescence and infrared spectroscopy, transmission electron microscopy, wide-angle X-ray scattering, and oscillatory rheometry. Titration experiments revealed a substantially shifted apparent pK(a) transition for Fmoc-FG, Fmoc-GG, and Fmoc-GF. The apparent pK(a) values observed correlated with the hydrophobicity (log P) of the Fmoc-dipeptide mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
231
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(256 citation statements)
references
References 52 publications
(107 reference statements)
24
231
0
1
Order By: Relevance
“…These values are comparable to measurements for peptide gels such as amyloid tapes [32][33][34] and spider silk [35,36]. Fig.…”
supporting
confidence: 86%
“…These values are comparable to measurements for peptide gels such as amyloid tapes [32][33][34] and spider silk [35,36]. Fig.…”
supporting
confidence: 86%
“…86 This is perhaps surprisingly high for the terminal carboxylic acid of a dipeptide, but this is a common observation for this kind of gelator. [86][87][88] In fact, the apparent pK a depends on the hydrophobicity of the gelator, the concentration in solution, and the solution temperature, and should probably be interpreted as the apparent pK a of the self-assembled aggregate. In analogy with other systems, close packing of carboxylates and carboxylic acids results in an increase in the pK a .…”
Section: Process Of Assemblymentioning
confidence: 99%
“…As mentioned above, for gelators such as 2NapFF, where the gelation can be controlled by the protonation of the terminal carboxylic acid, we and others have observed that the apparent pK a of this carboxylic acid is affected by the hydrophobicity of the gelator; the higher the hydrophobicity, the higher the apparent pK a . 87 Hence, if two gelators with sufficiently different pK a are mixed and the pH can be decreased in a controlled manner, self-sorting should be favored. Using the hydrolysis of GdL to slowly lower the pH allowed us to produce self-sorted systems.…”
mentioning
confidence: 99%
“…[15][16][17][18] A number of chemical and physical means have been used as a trigger to initiate self-assembly and to influence the produced nanostructures. [19][20][21][22][23][24] In particular, the biocatalytically triggered self-assembly of aromatic peptide amphiphiles enables control of the self-assembly process under constant and physiological conditions. 25 Xu et al was the first to exploit enzymatic self-assembly of Fmoc-amino acid using an alkaline phosphatase to dephosphorylate Fmoc-tyrosine phosphate (Fmoc-Yp) under basic conditions, forming a hydrogel, 26 but many more followed.…”
Section: Introductionmentioning
confidence: 99%